The First International Seminar Poltekkes Kemenkes Palangka Raya: A Journey Full of Meaning - Yeyentimalla, Yeyentimalla; Sera, Agnescia Clarissa; Sinaga, Doni Marisi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2022)
Poltekkes Kemenkes Palangka Raya in collaboration with Indonesian Scholars' Alliance and Global Health Management Journal (GHMJ) successfully held the first international seminar on November 9, 2020. The seminar which took place online in the midst of the raging Coronavirus Disease 2019 (COVID-19) pandemic raised the theme